2010
DOI: 10.1097/qad.0b013e3283333639
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after virologic failure of first-line ART in South Africa

Abstract: Virologic monitoring linked to resistance testing helped demonstrate the efficacy of lopinavir/ritonavir-containing second-line regimens in South Africa. A switch to second-line regimens in patients with virologic failure and drug resistance has substantial and rapid immunological and clinical benefits. Resistance testing identified a high-risk group without resistance who might benefit from increased medication access and/or adherence support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 10 publications
8
52
0
Order By: Relevance
“…In the group of patients treated with boosted PI, neither the presence of NRTI-associated mutations nor the history of previous suboptimal therapy were associated with virologic response, while in the group that received unboosted PI, the GSS score and the occurrence of single TAMs were associated with virological response. A similar result has been reported in a cohort of patient failing the salvage regimen after NNRTI failure [21]. A retrospective study on patients who failed an initial NNRTI-based regimen with M184V showed that a regimen comprising a boosted PI plus emtricitabine or lamivudine and a NRTI were as effective as the same regimen plus an additional agent [22].…”
Section: Discussionsupporting
confidence: 69%
“…In the group of patients treated with boosted PI, neither the presence of NRTI-associated mutations nor the history of previous suboptimal therapy were associated with virologic response, while in the group that received unboosted PI, the GSS score and the occurrence of single TAMs were associated with virological response. A similar result has been reported in a cohort of patient failing the salvage regimen after NNRTI failure [21]. A retrospective study on patients who failed an initial NNRTI-based regimen with M184V showed that a regimen comprising a boosted PI plus emtricitabine or lamivudine and a NRTI were as effective as the same regimen plus an additional agent [22].…”
Section: Discussionsupporting
confidence: 69%
“…[1][2][3] HIV drug resistance data emerging from South Africa have generally revealed patterns similar to those seen in HIV-1 subtype B virus. [4][5][6] In contrast to other countries in sub-Saharan Africa, studies from South Africa have reported fewer thymidine analogue mutations (TAMs) at failure of first-line ART, likely to be related to the use of viral load (VL) monitoring in the public sector program.…”
Section: Introductionmentioning
confidence: 82%
“…High rates of acquired drug resistance suggest poor adherence (which can be improved with better counseling and minimizing supply stock-outs), suboptimal regimens, and a lack of monitoring for failure to reduce the continuing use of a failing regimen[58–60]. Drug-resistance monitoring programs in RLSs are limited by cost and laboratory availability [61]. Currently, the WHO recommends universal clinical monitoring for patients receiving ART in RLSs and symptom-directed laboratory monitoring for safety and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Many individual country guidelines, however, recommend only clinical monitoring due to insufficient access to routine laboratory testing [11]. Immunologic and virologic testing have widely accepted clinical benefits, and examination of the cost-effectiveness of these strategies will prove an important part of developing and implementing new monitoring strategies [61]. In the absence of laboratory monitoring, strategies to monitor and improve treatment delivery and patient adherence may help minimize sustained virological failure more than clinical monitoring alone [52, 63].…”
Section: Discussionmentioning
confidence: 99%